Sweet Melody or Jazz? Transcription Around DNA Double-Strand Breaks - Long, Qilin; Liu, Zhichao; Gullerova, Monika (Frontiers in Molecular Biosciences, 2021)
The genomic integrity is continuously threatened by thousands of endogenous and exogenous damaging factors. In order to preserve genome stability, cells developed comprehensive DNA damage response (DDR) pathways that mediate the recognition of damaged DNA lesions, activation of signalling cascades and execution of DNA repair. Transcription has been understood to pose a threat to genome stability in the presence of DNA breaks. Interestingly, accumulating evidence in recent years shows that the transient transcriptional activation at DNA double-strand break (DSB) sites is required for efficient repair, whilst the rest of the genome exhibits temporary transcription silencing. This genomic shut down is a result of multiple signalling cascades involved in the maintenance of DNA/RNA homeostasis, chromatin stability and genome fidelity. Regulation of transcription of protein-coding genes and non-coding RNAs has been extensively studied, however, the exact regulatory mechanisms of transcription at DSBs remain enigmatic. These complex processes involves many players such as transcription-associated protein complexes, including kinases, transcription factors, chromatin remodelling complexes and helicases. The damage-derived transcripts themselves also play an essential role in DDR regulation. In this review, we summarise the current findings on the regulation of transcription at DSBs and discuss the roles of various accessory proteins in this process and consequently in DDR.